Effect Of Chitin Synthesis Inhibitors On Rice Swarming Caterpillar Spodoptera Mauritia And Rice Moth Corcyra Cephalonica And A Larval Parasitoid Bracon Brevicornis - Prathapan K D (Department of Agricultural Entomology, College of Agriculture, 1991)
Effects of four chitin synthesis inhibitors viz. diflubenzuron, chlorfluazuron, PH 70-23 and BASF LAB 153 959 I were assessed on two insect pests, the rice swarming caterpillar Spodoptera mauritia ( Boisduval) and rice moth Corcyra cephalonica (Stainton) and on its larval parasitoid Bracon brevicornis (Wesmael). Ovicidal action was assessed by treating one and two-day old eggs of S. mauritia in aqueous and mathanilic media. It was low in aqueous medium. But in methanolic medium diflubenzuron and the highest doses of the other three compounds showed enhanced action. In general, high ovicidal action was observed in methanolic medium. There was no significant difference between one and two-day old eggs in their susceptibility to chitin synthesis inhibitors. Chlorfluazuron was the most toxic causing cent per cent mortality at doses as low as 2 x 10 -5% when treated on second and fifth instar larvae of S. mauritia. Diflubenzuron, PH 70-23 and BASF LAB 153 959 I were also highly effective. Second instar larvae were more susceptible than fifth instar ones. Besides stomach action, a high degree of contact action was also observed. Final instar larvae of S. mauritia when treated with the test chemicals, produced larval-pupal intermediates and caused pupal mortality and emergence of deformed adults. All the four moult inhibitors were highly active during larval – pupal transformations. Pupae were less susceptible to chitin synthesis inhibitors. Yet, some treatments caused mortality and emergence of deformed adults. Chlorfluazuron was the most toxic to pupae. Fecundity, hatchability of eggs and longevity were reduced when the male moths of S. mauritia were fed on sugar solution containing the moult inhibitors. Antifeedant action of the chitin synthesis inhibitors was found to be less pronounced. Residual effect of all the four compounds persisted on the treated rice foliage throughout a study period of 36 days. But the efficacy of residues exposed to sunlight and rain was very low. Ovicidal action of the moult inhibitors was low to moderate on one and four-day old eggs of C. cephalonica in aqueous medium. In methanolic medium diflubenzuron at 2 x 10 -1 %, 2 x 10 -2 % and 2 x 10 -3 % and PH 70-23 and BASF LAB 153 959 I at 2 x 10 -1 % caused enhanced ovicidal action. In general there was no significant difference between the susceptibility of one and four-day old eggs. Chlorfluazuron was found to be the most toxic compound against larvae of C. cephalonica followed by BASF LAB 153 959 I. Diflubenzuron and PH 70-23 were less effective. Early larval instars were more susceptible. Contact action of compounds other than chlorfluazuron was low. Larval – pupal intermediates, pupal mortality and emergence of deformed adults were resulted when the last instar larvae of C. cephalonica were treated with the chemicals. Chlorfluazuron was found to be the most toxic compound. Prepupal treatment also caused the above juvenomimetic effects. But treatments other than chlorfluazuron 2 x 10 – 2% were less effective. Treatment of pupae of C. cephalonica resulted in pupal mortality and emergence of deformed adults. But pupae were less susceptible to the moult inhibitors as compared to the larval stages. External application of Chitin synthesis inhibitors to moths of C. cephalonica had no adverse had no adverse effect on fecundity, hatchability of eggs and longevity of the treated moths. Chlorfluazuron was found to inhibit the emergence of adult parasites from treated hosts and adversely affect the progeny production of B. brevicornis. Diflubenzuron, PH 70-23 and BASF LAB 153 959 I were non-toxic or only slightly toxic to the parasite.